Lessons learned in 20 years of endoscopic endonasal surgery for pterygopalatine and infratemporal fossae lesions: analysis of a patient series and systematic review of literature - Zoli, Matteo; Sollini, Giacomo; Giorli, Alessia; Carretta, Alessandro; Magnani, Marcello; Rustici, Arianna; Conti, Martina; Belotti, Laura Maria Beatrice; Zenesini, Corrado; Asioli, Sofia; Farneti, Paolo; Pasquini, Ernesto; et al. (Frontiers in Oncology, 2025)
IntroductionRecently, the endoscopic endonasal approach (EEA) has been proposed as a possible surgical option for benign and malignant tumors, located in the infratemporal (ITF) and pterygopalatine fossae (PPF). The aim of this study is to analyze the surgical outcome of the EEA for these lesions, identifying the preoperative factors affecting tumor resection.Materials and methodsAll consecutive cases of PPF and ITF tumors operated through an EEA have been retrospectively collected. Preoperative clinical and radiological features, surgical outcome, complications and patient follow-up have been analyzed. A systematic review of literature has been performed.ResultsThe series includes 100 patients (66 males, 66.0%, mean age: 43.7 ± 22.1). The most common histotypes were juvenile angiofibromas (36 cases, 36.0%), malignancies (26, 26.0%), and chordomas (14, 14.0%). Gross total resection of the PPF/ITF portion of the tumor was achieved in 88 (88.0%) patients. The most common complication was represented by 10 cases (10.0%) of V2 hypoesthesia (3 transient). At logistic regression, tumor location in the temporo-masseteric and tubo-pharyngeal zones proved negatively associated with the GTR rate (p:0.05, p<0.01).ConclusionEEA is an effective and safe approach for both benign and malignant tumors involving the PPF and ITF. It is characterized by a favorable complications rate and a quick patients recovery. We observed that the tumor extensions in the temporo-masseteric area and in the tubo-pharyngeal space were the most relevant factors negatively associated with complete tumor removal.